Dnmt3b is a haploinsufficient tumor suppressor gene in Myc-induced lymphomagenesis - Vasanthakumar, Aparna (American Society of Hematology, 2013)
The drivers of abnormal DNA methylation in human cancers include widespread aberrant splicing of the DNMT3B gene, producing abnormal transcripts that encode truncated proteins that may act as dominant negative isoforms. To test whether reduced Dnmt3b dosage can alter tumorigenesis, we bred Dnmt3b(+/−) mice to Eµ-Myc mice, a mouse model susceptible to B-cell lymphomas. Eµ-Myc/Dnmt3b(+/−) mice showed a dramatic acceleration of lymphomagenesis, greater even than that observed in Eµ-Myc mice that express a truncated DNMT3B isoform found in human tumors, DNMT3B7. This finding indicates that Dnmt3b can act as a haploinsufficient tumor suppressor gene. Although reduction in both Dnmt3b dosage and expression of DNMT3B7 within the Eµ-Myc system had similar effects on tumorigenesis and DNA hypermethylation, different molecular mechanisms appear to underlie these changes. This study offers insight into how de novo DNA methyltransferases function as tumor suppressors and the sensitivity of Myc-induced lymphomas to DNA methylation.